Keeping in touch: a benefit of public holidays - Joachim Merz; Lars Osberg (Institute for the Study of Labor (IZA), 2006)
This paper argues that public holidays facilitate the co-ordination of leisure time but do not constrain the annual amount of leisure. Public holidays therefore have benefits both in the utility of leisure on holidays and (by enabling people to maintain social contacts more easily) in increasing the utility of leisure on normal weekdays and weekends. The paper uses the variation (13 to 17) in public holidays across German Länder and the German Time Use Survey of 2001-02 to show that public holidays have beneficial impacts on social life on normal weekdays and weekends. Since these benefits are additional to the other benefits of holidays, it suggests that there is a case to be made for more public holidays.
Keywords: J22; I31; Z13; H40; 330; public holidays; social contacts; social leisure time; time allocation; time use diaries; German Budget Survey 2001/02; Freizeit; Freizeitverhalten; Soziale Beziehungen; Zeitbudgetforschung; Deutschland